Multidrug resistance and diversity of resistance profiles in carbapenem-resistant Gram-negative bacilli throughout a wastewater treatment plant in Colombia (2020)
ABSTRACT : Objectives: Carbapenem-resistant Gram-negative bacilli (CRGNB) have been reported in different wastewater treatment plants (WWTPs) throughout the world; however, few studies have described the antimicrobial resistance profile in different CRGNB throughout WWTPs, information that would identify points of selection of resistant bacteria. The objective of this work was to characterize the resistance profile of CRGNB harbouring blaKPC-2 from a Colombian WWTP. Methods: Six samples were taken from four points of a WWTP. CRGNB were selected in chromID1 CARBA and identified by 16S rRNA. Carbapenemases were determined by polymerase chain reaction (PCR), and susceptibility was assessed using VITEK2. Results: One hundred and forty-two CRGNB harbouring blaKPC-2 were detected: 41% corresponded to Aeromonas spp. (n = 58) and 59% to Enterobacteriaceae. To establish the resistance profile, 50% of the isolates were selected proportionally by family and sampling point (26 Aeromonadaceae and 45 Enterobacteriaceae). All Enterobacteriaceae showed resistance to carbapenems and penicillins + inhibitors, high percentages of resistance to ceftriaxone (88.9%), and ciprofloxacin (44.4%), and low resistance to other antibiotics (>30%). In Aeromonadaceae, 76.9% were resistant to ceftriaxone, 58% to carbapenems, and 65.4% to ciprofloxacin. Twenty-one resistance profiles were observed, the most common of which were resistant to penicillins + inhibitor, cephalosporins (third to fourth generation), and carbapenems (19%). The percentage of multidrug resistance was 91% and was similar at all points of the WWTP. Conclusions: The high frequency of multidrug resistance and great diversity of resistance profiles observed throughout the WWTP is of concern, and shows the role of WWTP as a reservoir and dissemination source of antimicrobial resistance to water sources.